Potential Use of Biomarker γ-H2AX on Peripheral Blood Patient Who Underwent Radioiodine Ablation Treatment in Indonesia - IIN KURNIA HASAN BASRI (Indonesian Journal of Cancer, 2021)
Thyroid cancer is one of the most common endocrine malignancies. Although the 10-year survival rate of differentiated thyroid cancer (DTC) is about 90% after conventional treatments, a small proportion of patients still suffer from tumor recurrence or drug resistance. DNA doublestrand breaks (DSBs) are important cellular lesions that can result from ionizing radiation exposure. The biomarker for DSB formation is the phosphorylated form of the histone H2 variant H2AX (γ-H2AX). We propose the use of γ-H2AX as a DNA DSB biomarker in thyroid cancer patients receiving radioiodine treatment as a possibility to detect the potential of instability genome after receiving the treatment. Evaluating DNA DSB damage with γ-H2AX biomarker might be important in managing thyroid cancer.